2007
DOI: 10.1096/fj.06-6551com
|View full text |Cite
|
Sign up to set email alerts
|

The role ofCaenorhabditis elegansinsulin‐like signaling in the behavioral avoidance of pathogenicBacillus thuringiensis

Abstract: Pathogens cause damage, and their elimination requires activation of the costly immune response. A highly economic defense strategy should thus be the behavioral avoidance of pathogens, as manifested in humans by all aspects of hygiene or revulsion at pathogen-rich material. Despite its potential importance, behavioral defenses have as yet received only little attention in biomedical research--in stark contrast to the physiological immune system. In the present study, the genetics of such behavioral defenses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 60 publications
3
67
1
Order By: Relevance
“…C. elegans protects itself from potential pathogenic bacteria by avoidance behaviour and innate immunity pathways (Pujol et al, 2001;Nicholas and Hodgkin, 2004;Kurz and Ewbank, 2003). Avoidance behaviour of C. elegans has been recorded for B. thuringiensis, S. marcescens, P. aeruginosa, P. luminescens and M. nematophila using different molecular mechanisms (Pujol et al, 2001;Pradel et al, 2007;Yook and Hodgkin, 2007;Zhang et al, 2005;Beale et al, 2006;Schulenburg and Müller, 2004;Sicard et al, 2007;Hasshoff et al, 2007). In our experiments, bacteria that cause mortality to P. pacificus tend to score low in the chemotaxis index, ranging from -0.09±0.04 for Serratia sp.…”
Section: P a U R A N T I A C A E N T E R O B A C T E R S Pmentioning
confidence: 65%
“…C. elegans protects itself from potential pathogenic bacteria by avoidance behaviour and innate immunity pathways (Pujol et al, 2001;Nicholas and Hodgkin, 2004;Kurz and Ewbank, 2003). Avoidance behaviour of C. elegans has been recorded for B. thuringiensis, S. marcescens, P. aeruginosa, P. luminescens and M. nematophila using different molecular mechanisms (Pujol et al, 2001;Pradel et al, 2007;Yook and Hodgkin, 2007;Zhang et al, 2005;Beale et al, 2006;Schulenburg and Müller, 2004;Sicard et al, 2007;Hasshoff et al, 2007). In our experiments, bacteria that cause mortality to P. pacificus tend to score low in the chemotaxis index, ranging from -0.09±0.04 for Serratia sp.…”
Section: P a U R A N T I A C A E N T E R O B A C T E R S Pmentioning
confidence: 65%
“…Previous studies have shown that C. elegans exhibits avoidance behavior when challenged with different pathogens (39). B. thuringiensis was one of the pathogens that C. elegans strongly avoided (40). Other nematode-pathogenic Bacillus spp., such as B. nematocida, evolved strategies to attract nematodes (41).…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that the food-leaving decision would be regulated by postingestive inputs (e.g., nutritional state or feeding history). Insulin signaling has previously been linked to perception of feeding state and food-related behavioral plasticity (30)(31)(32)(33). This finding prompted us to analyze adaptive food-leaving in mutants defective in the insulin pathway.…”
Section: Insulin and Tgf-β Mediators Of Nutritional State And Enviromentioning
confidence: 99%